Investigation of suppression of Υ⁡ (nS) in relativistic heavy-ion collisions at √sNN= 200 GeV and 5.02 TeV - Kim, Junlee; Park, Jaebeom; Hong, Byungsik; Hong, Juhee; Kim, Eun-Joo; Kim, Yongsun; Kweon, MinJung; Lee, Su Houng; Lim, Sanghoon; Seo, Jinjoo (Physical review, 2025)
The primary purpose of studying quarkonium production in relativistic heavy-ion collisions is to understand the properties of the quark-gluon plasma. At various collision systems, measurements of quarkonium states of different binding energies, such as Υ⁡(𝑛⁢𝑆), can provide comprehensive information. A model study has been performed to investigate the modification of Υ⁡(𝑛⁢𝑆) production in Pb-Pb collisions at √𝑠𝑁⁢𝑁=5.02TeV and Au-Au collisions at √𝑠𝑁⁢𝑁=200GeV. A Monte Carlo simulation study is performed with a publicly available hydrodynamic simulation package for the quark-gluon plasma medium and a theoretical calculation of the temperature-dependent thermal width of Υ⁡(𝑛⁢𝑆) considering the gluodissociation and inelastic parton scattering for dissociation inside the medium. In addition, we perform a systematic study with different descriptions of initial collision geometry and formation time of Υ⁡(𝑛⁢𝑆) to investigate their impacts on yield modification. The model calculation with a varied parameter set can describe the experimental data of Υ⁡(𝑛⁢𝑆) in Pb-Pb collisions at 5.02 TeV and Υ⁡(2⁢𝑆) in Au-Au collisions at 200 GeV but underestimates the modification of Υ⁡(1⁢𝑆) at the lower collision energy. The nuclear absorption mechanism is explored to understand the discrepancy between the data and simulation.